ANALISIS DAN PERANCANGAN SISTEM INFORMASI E-COMMERCE PADA DISTRO SUCKSME STORE JAMBI - Saefudin, Saefudin; Siahaan, Kondar (LPPM Universitas Dinamika Bangsa, 2020)
Sucksme Store Distro is a sales shop that is engaged in fashion styles such as various kinds of T-shirts, shirts,pants, shoes, backpacks, etc., on the Sucksme Store Store has supporters in marketing their merchandise,because currently distro customers can only be visited visited by the shop to make product purchases, as wellas product promotion by word of mouth, as well as long distance from the store location. Then designed anE-Commerce Information System at Sucksme Store Jambi Distro with the aim to facilitate product marketing,increase sales and reduce expenditure costs. In this study using prototyping modeling, it is expected that theresults of this study provide customers to make purchases, bookings and payment confirmation. As well asadministrators can manage item data, memeber data, ordering data and product purchases. For the futureanalysis and design of e-Commerce systems can be developed such as being able to exchange messagesbetween potential buyers and managers of Sucksme Store Jambi Distro.